Innovation Systems - Do they exist? Exploring Luhmanns thinking - Jorge Bateira (European Regional Science Association (ERSA), 2005)
Following Nelson and Winter's (1982) evolutionary critique of neoclassical view of technical change and economic growth, there appeared an abundant literature on National Innovation Systems (NIS) putting an emphasis on learning processes and institutions as important factors that shape the specific dynamics of growth in each country. Some scholars extended the discussion to sub-national territories, thereby giving origin to a new approach to regional development based on the concept of Regional Innovation Systems (RIS). Production and transfer of knowledge, and the role of institutions, are two major research domains in those strands of economics literature. However, the first one is largely dominated by H. Simon' cognitivism, which is under serious critique from an interactivist-constructivist perspective; the second is mostly descriptive, lacking a theoretical discussion about the ontology of institutions. The paper critically discusses the theoretical assumptions usually adopted in the IS literature, and proposes conceptual alternatives. The latter provide a theoretical framework more close to the sociological research and lead to serious doubts that innovation processes organise into systems.
Keywords: 330